Rancangan Berkelanjutan Rumah Kargo Kontainer dengan Sistem Modular di Jakarta Utara - Prawata, Albertus (Bina Nusantara University, 2012)
Sustainable home design implements a sustainability system , in which the design can meet the needs of both current and future residents as well as the environment. Sustainable design is applied in order to save the environment and natural resources by minimizing its use. The house is designed as a whole by considering the management of water, waste and electricity. Social interactions and relationships between the environment and the residents nearby are also expected to be sustainable. Regarding to the needs of residents of the city whichare diverse and dense, the house design implements a modular system, with the container material which suits the needs of its inhabitants. The modular system is objected to make easy the house improvement, assembility, and material reusage. Prefabricated process is also implemented, considering the transportation and construction. Thus the range of sustainable home design with modular systems in a dense region of North Jakarta meets the needs of the community and contributes to environment sustainability.